2011
DOI: 10.1061/(asce)gt.1943-5606.0000531
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Capacity of Spatially Random Cohesive Soil Using Numerical Limit Analyses

Abstract: This paper describes a probabilistic study of the two dimensional bearing capacity of a vertically loaded strip footing on spatially random, cohesive soil using Numerical Limit Analyses (NLA-CD). The analyses uses a Cholesky Decomposition (CD) technique with mid-point discretization to represent the spatial variation in undrained shear strength within finite element meshes for both upper and lower bound analyses, and assumes an isotropic correlation length. Monte Carlo simulations are then used to interpret th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 16 publications
5
28
0
Order By: Relevance
“…1b showed that the probability of failure gradually decreased with increase of correlation length for FOS=3.0. The results from Kasama and Whittle (2011) are much lower than other data points and decreasing nearly to zero. Therefore, it requires some justifications on these different FEM methods.…”
Section: Isotropic Studiesmentioning
confidence: 53%
See 4 more Smart Citations
“…1b showed that the probability of failure gradually decreased with increase of correlation length for FOS=3.0. The results from Kasama and Whittle (2011) are much lower than other data points and decreasing nearly to zero. Therefore, it requires some justifications on these different FEM methods.…”
Section: Isotropic Studiesmentioning
confidence: 53%
“…3. The effect of anisotropic conditions for FOS=2.0 and 3.0 were presented and compared with Kasama and Whittle's results (Kasama and Whittle, 2011) in Fig. 3a&b.…”
Section: Anisotropic Studiesmentioning
confidence: 96%
See 3 more Smart Citations